2011
DOI: 10.1111/j.1365-246x.2010.04922.x
|View full text |Cite
|
Sign up to set email alerts
|

Secular gravity variation at Svalbard (Norway) from ground observations and GRACE satellite data

Abstract: S U M M A R YThe Svalbard archipelago, Norway, is affected by both the present-day ice melting (PDIM) and Glacial Isostatic Adjustment (GIA) subsequent to the Last Pleistocene deglaciation. The induced deformation of the Earth is observed by using different techniques. At the Geodetic Observatory in Ny-Ålesund, precise positioning measurements have been collected since 1991, a superconducting gravimeter (SG) has been installed in 1999, and six campaigns of absolute gravity (AG) measurements were performed betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 53 publications
4
40
1
Order By: Relevance
“…formed contemporaneously (Lindner et al 1991). The geodetic observatory at Ny−Ålesund has been recording GPS measurements since 1991 while a supercon− ducting gravimeter to monitor the effect of present−day ice melting and glacial iso− static adjustment was installed in 1999 (Mémin et al 2011). The results have shown that the mean isostatic uplift rate is around 8.5 mm/year while the rate of uplift from 2003 to 2006 was two and a half times greater than it had been during the preceding period (11.2 mm/year against 4.8 mm/year) see Kierulf et al (2009), Omang andKierulf (2011).…”
Section: Discussionmentioning
confidence: 99%
“…formed contemporaneously (Lindner et al 1991). The geodetic observatory at Ny−Ålesund has been recording GPS measurements since 1991 while a supercon− ducting gravimeter to monitor the effect of present−day ice melting and glacial iso− static adjustment was installed in 1999 (Mémin et al 2011). The results have shown that the mean isostatic uplift rate is around 8.5 mm/year while the rate of uplift from 2003 to 2006 was two and a half times greater than it had been during the preceding period (11.2 mm/year against 4.8 mm/year) see Kierulf et al (2009), Omang andKierulf (2011).…”
Section: Discussionmentioning
confidence: 99%
“…Past GRACE studies in this region suggested the rate as 8.8 ± 3 Gt yr -1 (Wouters et al 2008), 9.1 ± 1.1 Gt yr -1 (Mémin et al 2011), and 3 ± 2 Gt yr -1 (Jacob et al 2012). The latest estimate by Jacob et al (2012) is considerably smaller than the two earlier estimates.…”
Section: Svalbardmentioning
confidence: 99%
“…The latest estimate by Jacob et al (2012) is considerably smaller than the two earlier estimates. This difference would reflect the inclusion of the GRACE data after 2009, i.e., Jacob et al (2012) included the data up to 2010.12 while Wouters et al (2008) and Mémin et al (2011) used those up to 2008.01 and 2009.01, respectively. As described before, Svalbard shows significant mass increase around the 2009/2010 winter.…”
Section: Svalbardmentioning
confidence: 99%
“…Peltier, 2004;Steffen et al, 2009;Mazzotti et al, 2011;Memin et al, 2011;Sato et al, 2012), while the relationship between surface gravity change and uplift rates can be employed to constrain GIA in regions where ice history and Earth structure are poorly known (e.g. Wahr 425 et al, 1995;Purcell et al, 2011;van Dam et al, 2017 …”
Section: Gravity Datamentioning
confidence: 99%